2020
DOI: 10.3389/fimmu.2020.01300
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Regulates Proliferation, Migration and Invasion of Synoviocytes in Rheumatoid Arthritis via JNK Signaling

Abstract: Activated fibroblast-like synoviocytes (FLSs) play a central role in the formation of synovial pannus and joint destruction in rheumatoid arthritis (RA). Targeting FLSs could be a potential therapeutic strategy. The objective of this study is to explore the role of c-Jun N-terminal kinase (JNK) in proliferation, migration and invasion of FLSs promoted by the sonic hedeghog (SHH) signaling pathway in patients with RA. Activation of SHH signaling was evaluated by real-time PCR and Western Blot. Levels of phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Perhaps the observed counter-regulation of Pde4c is particularly pertinent to current translational strategies given the recent strong interest in the therapeutic potential of PDE4 inhibitors in RA as well as a wide range of other chronic inflammatory conditions including psoriatic arthritis, for which Apremilast was recently approved as a treatment 90 : indeed, ES-62 further acts to promote cAMP signalling in SFs by inducing inverse methylation signatures in the 1 st Exon region of other important elements, including Adcy10 (adenylate cyclase 10), AKAPs (A-kinase anchoring proteins) and Prkacb (Protein kinase A catalytic subunit beta) to those of naïve- and CIA-SFs. Interestingly therefore, in the context of ES-62 targeting this anti- inflammatory pathway, cilia provide a spatiotemporal platform for compartmentalising elements of the cAMP signalsome to promote protein kinase A-mediated antagonism of Hedgehog signalling 91 , a key pathway regulating cell differentiation which has recently been implicated in the proliferation, migration and invasion of RA SFs 92 . Moreover, recent mathematical modelling of differential gene expression metadata from a number of studies in healthy and RA synovial tissue 93 identified a gene signature panel representing an interactive biological network of hub (STAT1, RAC2 and KYNU) proteins and effector molecules (PEPD receptor and NR4A1, MEOX2, KLF4, IRF1 and MYB transcription factors and miRs-146a, -299, -3659, -6882 and - 8078) that provides a platform for validation of pathogenic mechanisms and potentially, a predictive tool for diagnosis and development of effective treatment strategies for RA: apart from KYNU and miR-299 (miRs-3659, -6882 and -8078 were not identified in our methylome study), these “signature” genes were differentially methylated at one or more sites in naïve-, CIA- and ES-62-CIA-SFs (Supplementary Information Table 2), with CIA- and ES-62 SFs generally exhibiting inverse profiles of methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the observed counter-regulation of Pde4c is particularly pertinent to current translational strategies given the recent strong interest in the therapeutic potential of PDE4 inhibitors in RA as well as a wide range of other chronic inflammatory conditions including psoriatic arthritis, for which Apremilast was recently approved as a treatment 90 : indeed, ES-62 further acts to promote cAMP signalling in SFs by inducing inverse methylation signatures in the 1 st Exon region of other important elements, including Adcy10 (adenylate cyclase 10), AKAPs (A-kinase anchoring proteins) and Prkacb (Protein kinase A catalytic subunit beta) to those of naïve- and CIA-SFs. Interestingly therefore, in the context of ES-62 targeting this anti- inflammatory pathway, cilia provide a spatiotemporal platform for compartmentalising elements of the cAMP signalsome to promote protein kinase A-mediated antagonism of Hedgehog signalling 91 , a key pathway regulating cell differentiation which has recently been implicated in the proliferation, migration and invasion of RA SFs 92 . Moreover, recent mathematical modelling of differential gene expression metadata from a number of studies in healthy and RA synovial tissue 93 identified a gene signature panel representing an interactive biological network of hub (STAT1, RAC2 and KYNU) proteins and effector molecules (PEPD receptor and NR4A1, MEOX2, KLF4, IRF1 and MYB transcription factors and miRs-146a, -299, -3659, -6882 and - 8078) that provides a platform for validation of pathogenic mechanisms and potentially, a predictive tool for diagnosis and development of effective treatment strategies for RA: apart from KYNU and miR-299 (miRs-3659, -6882 and -8078 were not identified in our methylome study), these “signature” genes were differentially methylated at one or more sites in naïve-, CIA- and ES-62-CIA-SFs (Supplementary Information Table 2), with CIA- and ES-62 SFs generally exhibiting inverse profiles of methylation.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are downstream of TLR4 and play important roles in the pathogenesis of RA, as the abnormal activation of JNK and p38 almost participate in all aspects of RA-related pathologies [ 21 , 22 , 23 , 24 ]. To study the effects of rosmanol, carnosol, and their combination on the MAPKs, the expression levels of JNK, p-JNK, p38, and p-p38 in synovial tissue were examined by Western blot on day 42 ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…MAPK family proteins, including the extracellular-signal-regulated kinases, c-Jun N-terminal kinase (JNK), and p38 in mammals, are tightly associated with RA pathogenesis [ 20 ]. JNK regulates the expression of matrix metalloproteinases (MMPs), as well as the proliferation, migration, and invasion of synoviocytes and the destruction of joints [ 21 , 22 ]. P38 is critical for RA pathogenesis, as its activation involves almost all aspects of RA-related pathologies, including the expression of pro-inflammatory cytokines, synovitis, cartilage degradation, bone destruction, and angiogenesis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…SHH regulates progenitor cell proliferation and differentiation in a concentration-dependent manner ( Lin et al, 2014 ). In adult, SHH acts as an oncogene to transform adult stem cells to cancer stem cells and is involved in tumorigenesis of many types of cancer ( Ali et al, 2019 ; Zhu et al, 2020 ). However, aside from cancer, the role of SHH in adult human tissue degeneration and aging-associated degenerative diseases was not well documented.…”
Section: Discussionmentioning
confidence: 99%
“…The hedgehog protein family, including Sonic Hedgehog (SHH) and Indian Hedgehog (IHH), have been shown to play an important role during skeletal development and homeostasis ( Alman, 2015 ; Zhu et al, 2020 ). While SHH is expressed by mesenchymal progenitor cells during limb bud patterning ( Alman, 2015 ; Tan et al, 2018 ), IHH is expressed by pre-hypertrophic chondrocytes within the growth plate ( Zhou J. et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%